Drivers of declining CO2 emissions in 18 developed economies - Le Quere, C; Korsbakken, JI; Wilson, C; Tosun, J; Andrew, R; Andres, RJ; Canadell, JG; Jordan, A; Peters, GP; van Vuuren, DP (Springer Nature, 2019)
Global emissions of carbon dioxide (CO2) from fossil fuels and industry increased by 2.2% per year on average between 2005 and 20151. Global emissions need to peak and decline rapidly to limit climate change to well below 2 °C of warming2,3, which is one of the goals of the Paris Agreement4. Untangling the reasons underlying recent changes in emissions trajectories is critical to guide efforts to attain those goals. Here we analyse the drivers of decreasing CO2 emissions in a group of 18 developed economies that have decarbonized over the period 2005–2015. We show that within this group, the displacement of fossil fuels by renewable energy and decreases in energy use explain decreasing CO2 emissions. However, the decrease in energy use can be explained at least in part by a lower growth in gross domestic product. Correlation analysis suggests that policies on renewable energy are supporting emissions reductions and displacing fossil fuels in these 18 countries, but not elsewhere, and that policies on energy efficiency are supporting lower energy use in these 18 countries, as well as more widely. Overall, the evidence shows that efforts to reduce emissions are underway in many countries, but these efforts need to be maintained and enhanced by more stringent policy actions to support a global peak in emissions followed by global emissions reductions in line with the goals of the Paris Agreement3.